Electronic Ticketing Implementation (E-Ticketing) to Traffic Violations in the Banyumas Regency - Cahya Suryana (Faculty of Law Universitas Muhammadiyah Purwokerto, 2021)
The implementation of electronic ticketing in Banyumas Regency begins with a trial period on February 3-10, 2019, and the implementation started on February 11, 2019. The application of electronic ticketing is still not understood by the public, and it can be seen that there are still intersections that do not use head guards or stop exceeding road markings. This study aims to see how the implementation of e-ticketing to traffic in Banyumas Regency under existing regulations. Furthermore, whether there are changes before and after the implementation of e-ticketing. This study uses an empirical juridical legal approach. How is the implementation of electronic ticketing (e-ticket) for traffic in Banyumas Regency? 2 What are the obstacles in implementing electronic ticketing in Banyumas Regency. When viewed from the Banyumas Regency tickets data period 2018 to 2019, there is still a significant increase and decrease due to several factors such as extended holidays, homecoming, and new e-ticketing, while from 2019 to 2020, there is an increase at the beginning of the year due to holidays long as well. After that, there was a significant decline due to the pandemic. Obstacles in the implementation of electronic ticketing (e-ticketing) in Banyumas Regency are in vehicle ownership problems. The number of CCTV (Closed Circuit Television) installed to monitor violators is still lacking because not all intersections have CCTV installed, especially in crowded areas. It is expected to add CCTV at every intersection that becomes a crowd point, which is expected to comply with traffic rules and has accidents. It is hoped that the Transportation Agency and the Police will be given more education about the application of e-ticketing in Banyumas Regency.Keywords: electronic ticketing and failure